From deaf to deaf: obtaining communication choice in an era of change - Smith, Magteld (Department of Communication Science, University of the Free State, 2005)
This opinion piece is from a "deaf' perspective. The writer's intention is not to list all the prevailing misconceptions and misunderstandings about deafness, deaf people, and sign language. Rather, it is to promote a line of thought and action that may lead people to undertake meaningful and effective programmes for the "deaf'. The arguments emanate from a combination of frustration and anger over the failure of hearing people to recognise and make appropriate use of deaf people's strengths, personal development, politics and, indeed, the exercise of choice.
Keywords: Deafness; Deaf people; Sign language; Hearing people